ENT Foreign Bodies: An Experience - Awad,Al Hussein (2018)
Abstract Introduction Ear, nose and throat (ENT) foreign bodies (FBs) are common occurrences, particularly among children. The proper recognition, study, and management of FBs are required to prevent complications. Their consequences are greatly variable, from mild disturbances that may not require hospitalization up to life-threatening complications. Objective To analyze the clinical spectrum of ENT FBs, the methods of removal, the outcomes and complications as seen in a tertiary referral hospital. Methods This hospital-based cross-sectional retrospective study was performed from July 2014 to June 2016. Patients with any type of ENT FBs, regardless of age, were included in the study; data was collected from 1,013 patients (572 males and 440 females) with a mean age of 12.5 years. Results Foreign bodies represented a large category among ENT emergencies (30%). Children were affected more frequently, particularly ≤ 6 years old. Swallowed FBs were themost common (53.6%), followed by aural FBs (24.68%), nasal FBs (19%), and inhaled FBs (2.6%). A total of 54.69% of ENT s were removed under general anesthesia (GA). Conclusion Foreign bodies (FB) in the ears, nose or throat are a common occurrence in otorhinolaryngology (ENT) emergency services. Children are the most affected age group. The commonest site of FB lodgment is in the throat. Ear, nose and throat FBs need to be properly managed to avoid complications.